2008
DOI: 10.1158/1055-9965.epi-07-0511
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Specific Membrane Antigen Expression Is a Potential Prognostic Marker in Endometrial Adenocarcinoma

Abstract: The aim of this study was to determine the role of prostate-specific membrane antigen (PSMA) as a prognostic marker in endometrial adenocarcinoma (EAC) and to explore whether its down-regulation could be due to epigenetic mechanism. First, we examined the expression and the prognostic value of PSMA by semiquantitative reverse transcription-PCR and immunohistochemistry in EAC tissue samples. Second, to explore the role of CpG methylation in down-regulation PSMA in EAC, we evaluated PSMA CpG island methylation u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…A recent microarray analysis on patient tissues revealed that strong AR expression was detected in benign prostate (83%), localized prostate cancer (100%), and lymph node metastasis (80%), but less (40%) in metastatic hormone-resistant prostate cancer (3). It was also noticed that two highly aggressive androgen-independent prostate cancer cell lines: DU145 and PC-3 are double-negative of AR and PSMA (29) and the loss of their AR and PSMA expression is due to epigenetic silencing by CpG island hypermethylation of their promoter regions (2931). The DU145 and PC-3 lines were derived from brain and bone metastases of prostate cancer, whereas the AR(+), PSMA(+) LNCaP cell line was derived from a lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent microarray analysis on patient tissues revealed that strong AR expression was detected in benign prostate (83%), localized prostate cancer (100%), and lymph node metastasis (80%), but less (40%) in metastatic hormone-resistant prostate cancer (3). It was also noticed that two highly aggressive androgen-independent prostate cancer cell lines: DU145 and PC-3 are double-negative of AR and PSMA (29) and the loss of their AR and PSMA expression is due to epigenetic silencing by CpG island hypermethylation of their promoter regions (2931). The DU145 and PC-3 lines were derived from brain and bone metastases of prostate cancer, whereas the AR(+), PSMA(+) LNCaP cell line was derived from a lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Mhawech-Fauceglia et al (2008) assessed PSA expression in 49 endometrial adenocarcinoma tissue specimens. The study reported weak expression of PSA in the glands of normal endometrium and that 67.7% of EC tissues had no/weak staining for PSA.…”
Section: Endometrial Cancermentioning
confidence: 99%
“…High PSA mRNA levels were associated with stage I disease but not with tumour grade or subtype. Interestingly, multivariate survival analysis associated loss of PSA expression with worse disease-free survival (Mhawech-Fauceglia et al 2008). Circulating levels of PSA are increased in women with PCOS and are directly correlated with hyperandrogenism (Mardanian & Heidari 2011).…”
Section: Endometrial Cancermentioning
confidence: 99%
“…7,8), PSMA (9), and PSCA (10,11). Although these protein targets are frequently expressed by prostate cancer cells, they are also expressed by normal prostate tissue and may not be critical for the survival of the tumor; hence, their expression might be downregulated by cancer cells during the course of immune targeting or disease progression (12)(13)(14)(15)(16). Thus, there remains a need to identify immune targets of prostate cancer that are highly expressed in metastatic disease and/or critical to the progression of the disease, as simultaneous antigen targeting may be important to prevent the outgrowth of escape variants arising during the course of targeted therapy.…”
Section: Introductionmentioning
confidence: 99%